2011
DOI: 10.1542/peds.2010-1675
|View full text |Cite
|
Sign up to set email alerts
|

Differential Growth Patterns Among Healthy Infants Fed Protein Hydrolysate or Cow-Milk Formulas

Abstract: WHAT'S KNOWN ON THIS SUBJECT:The different classes of formulas, and different brands within each class, vary in composition and flavor profiles, both of which may influence feeding and growth patterns. Because recent evidence suggests that, relative to intact proteins, hydrolyzed proteins are absorbed and metabolized in a way that promotes greater satiation, we conducted a randomized study on healthy, formula-fed infants to determine whether growth patterns and feeding behaviors differ on the basis of formula … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
90
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 122 publications
(97 citation statements)
references
References 54 publications
6
90
1
Order By: Relevance
“…Mennella et al (30) found that infants randomly assigned to an infant formula with hydrolyzed cow-milk protein, which has a high content of FAAs, ingested less formula compared with those receiving a normal cow-milkbased infant formula and had a growth pattern closer to that of breastfed infants. In another study, glutamate, one of the most abundant FAAs in hydrolyzed infant formula, was added to a cow-milk whole-protein infant formula (31).…”
Section: Faas and Appetitementioning
confidence: 99%
“…Mennella et al (30) found that infants randomly assigned to an infant formula with hydrolyzed cow-milk protein, which has a high content of FAAs, ingested less formula compared with those receiving a normal cow-milkbased infant formula and had a growth pattern closer to that of breastfed infants. In another study, glutamate, one of the most abundant FAAs in hydrolyzed infant formula, was added to a cow-milk whole-protein infant formula (31).…”
Section: Faas and Appetitementioning
confidence: 99%
“…Hydrolyzed protein may be more easily absorbed, metabolized differently, and exert different satiety responses than the modified cow's milk protein of standard formulas. A recent study that randomized healthy infants to receive either standard (cow's milk based) or hydrolyzed formula from 0.5 to 7.5 mo found higher WAZ starting at 3.5 mo, and higher WLZ starting at 2.5 mo among infants receiving standard formula, but no differences in LAZ (104). Individual amino acid composition may affect infant metabolism as well.…”
Section: Formula Versus Formula Feedingmentioning
confidence: 99%
“…Finally, mode of milk feeding may also be associated with growth curves: breastfed babies are less likely to be overweight or obese at 4 years than formula-fed babies [9]. The type of formula may also matter in relation to growth since in an experimental study, weight gain at ages 2.5 to 7.5 months in infants fed an extensively hydrolyzed protein formula was more normative than that of infants fed cow's milk formula [14]. However, a recent epidemiological report did not show a significant impact of type of formula used and growth at 4 months [15].…”
Section: Association Between Milk Feeding Practices and Later Eating mentioning
confidence: 99%